2011
DOI: 10.5507/fot.2011.007
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of the freshwater cyanobacterium "Phormidium" murrayi = Wilmottia murrayi.

Abstract: Abstract:The cyanobacterial genus Phormidium is polyphyletic, as follows from recent molecular and phenotypic analyses. Several isolated clusters were found also in Antarctic populations (taton et al. 2006(taton et al. , taton et al. 2010(taton et al. , Strunecký et al. 2010b. A few of them have already been described or revised on the generic level (e.g., Phormidesmis, Microcoleus). One of the separate clusters belongs to a group of strains identified traditionally as Phormidium murrayi, described from the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 30 publications
4
76
0
4
Order By: Relevance
“…In 16S rDNA analyses, both environmental samples grouped with Phormidium murrayi and Microcoleus glaciei (formerly P. murrayi) in the phylogenetic tree, but in different branches. Previous published studies found a similarly separated Phormidium murrayi clade in phylogenetic analyses, principally from Antarctic habitats (Casamatta et al, 2005;Taton et al, 2006b;Comte et al, 2007;Strunecký et al, 2011) but also from benthic freshwater mats in New Zealand (Heath et al, 2010); the clade was also found in a revision of the genus Microcoleus (Siegesmund et al, 2008). Casamatta et al (2005) reassigned P. murrayi to M. glaciei on the basis of phylogenetic and microscopical analyses and Comte et al (2007) confirmed the separation of P. murrayi from typical Phormidium species (e.g.…”
Section: Morphotype-genotype Iii: Oscillatoria Tenuissupporting
confidence: 61%
See 1 more Smart Citation
“…In 16S rDNA analyses, both environmental samples grouped with Phormidium murrayi and Microcoleus glaciei (formerly P. murrayi) in the phylogenetic tree, but in different branches. Previous published studies found a similarly separated Phormidium murrayi clade in phylogenetic analyses, principally from Antarctic habitats (Casamatta et al, 2005;Taton et al, 2006b;Comte et al, 2007;Strunecký et al, 2011) but also from benthic freshwater mats in New Zealand (Heath et al, 2010); the clade was also found in a revision of the genus Microcoleus (Siegesmund et al, 2008). Casamatta et al (2005) reassigned P. murrayi to M. glaciei on the basis of phylogenetic and microscopical analyses and Comte et al (2007) confirmed the separation of P. murrayi from typical Phormidium species (e.g.…”
Section: Morphotype-genotype Iii: Oscillatoria Tenuissupporting
confidence: 61%
“…Recently, Strunecký et al (2011) proposed the new genus Wilmottia, with the type species Wilmottia murrayi. Considering that this cyanobacterium was originally described as Lyngbya murrayi, and has subsequently been designated as Phormidium murrayi (Anagnostidis & Komárek, 1988), Microcoleus glaciei (Casamatta et al, 2005) and Wilmottia murrayi (Strunecký et al, 2011), this is clearly a problematic taxon in need of further research. We identified our morphotypes as P. corium on the basis of their separation from 'P.…”
Section: Morphotype-genotype Iii: Oscillatoria Tenuismentioning
confidence: 99%
“…Other studies which have used multiple strains to describe new taxa showed that the 16S rRNA gene sequence similarity can be as low as 98% within one species (cf. Siegesmund et al 2008, Strunecký et al 2011. Most of the T. desertorum strains had similarity values well above this number; however, there were three exceptions with values close to or considerably below 98%.…”
Section: Discussionmentioning
confidence: 85%
“…see Komárek 2010 for review of older works, afterwards e.g. Strunecký et al 2011;Komárek et al 2013;Komárková et al 2013;Dvořák et al 2014a). During the 19th Symposium of the International Society for Cyanophyte Research in 2013, 16 new genera were presented .…”
Section: Estimate Of the Total Cyanobacterial Biodiversitymentioning
confidence: 99%